Endurance evaluation with surface EMG during unilateral static balance in elite taekwondo athletes - Ramazanoglu, N. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Proper balance control is mainly based on muscular synergies that minimize displacements of the centre of the gravity while maintaining upright stance, proper orientation and adapt techniques imparted to the sport practised (10,5). Taek-won-do requires a unipedal posture to perform different technical movements (eg. kicking ). Purpose: The aim of this study was to to evaluate the activation patterns of M. Biceps femoris and M. Quadriceps Femoris of elite Taekwon-do athletes during unilateral stance. Method: Six national male Taek-won-do athletes ( age=22.8±2.5 years, sport age=10.6±4.2 years, height=173±5.5 cm, weight=66.5±6.3 kg, BMI=22±0.7) participated in the study. Surface EMG data were recorded from M. Biceps Femoris and M. Vastus Lateralis during the unipedal stance condition on the stabilometer. We asked to maintain right and left unilateral stance positions as long as possible. EMG Ag-AgCl (silver/silver chloride) surface disk electrodes were placed according to the recommendation by SENIAM. The amplifier EMG 100C was equipped with a band pass filter 10-500 Hz; gain was chosen 1000. The EMG signal was sampled at 2000 Hz. Results: Endurance time for the right leg was longer (429.9 s versus 298.4 s; p<0.05). According to EMG measurement, the subjects employed different muscle activation patterns as they became fatigued. M. Biceps Femoris mean EMG frequency was at 100 Hz for all measurements. For both stance conditions, the activation of M.Quadriceps Femoris (root mean square) and mean EMG frequency was higher. Also, alternating activation of the two muscles was also observed. There were no significant differences for Center of Pressure, Forward-Backward Standart Deviation, Medium-Lateral Standart Deviation, Average Forward-Backward Velocity, Average Medium-Lateral Velocity, Perimeter and Ellipse Area between unilateral left foot stance and right foot stance. Discussion: Elite male Taek-won-do athletes employ similar muscle activation strategies during unilateral stance, but endurance time is different for the right and left leg